2021
DOI: 10.3390/molecules26092475
|View full text |Cite
|
Sign up to set email alerts
|

Validated Stability-Indicating GC-MS Method for Characterization of Forced Degradation Products of Trans-Caffeic Acid and Trans-Ferulic Acid

Abstract: When dealing with simple phenols such as caffeic acid (CA) and ferulic acid (FA), found in a variety of plants, it is very important to have control over the most important factors that accelerate their degradation reactions. This is the first report in which the stabilities of these two compounds have been systematically tested by exposure to various different factors. Forced degradation studies were performed on pure standards (trans-CA and trans-FA), dissolved in different solvents and exposed to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Ionization of the ester group of the p ‐coumaric acid TMS derivative can take place on the double‐bonded oxygen or on the oxygen linked to the TMS group, giving ions a +● and b +● , respectively (Figure 2). Ion a +● can easily lose TMSO ● to give the ion c + at m/z 219.0835 strongly stabilized by conjugation 16 . However, low‐energy CID‐MS/MS analyses (Table 1) showed that this ion could also be produced from ion d + at m/z 293.1027 resulting from the loss of a methyl radical by the molecular ion b +● .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionization of the ester group of the p ‐coumaric acid TMS derivative can take place on the double‐bonded oxygen or on the oxygen linked to the TMS group, giving ions a +● and b +● , respectively (Figure 2). Ion a +● can easily lose TMSO ● to give the ion c + at m/z 219.0835 strongly stabilized by conjugation 16 . However, low‐energy CID‐MS/MS analyses (Table 1) showed that this ion could also be produced from ion d + at m/z 293.1027 resulting from the loss of a methyl radical by the molecular ion b +● .…”
Section: Resultsmentioning
confidence: 99%
“…to give the ion c + at m/z 219.0835 strongly stabilized by conjugation. 16 However, low-energy CID-MS/MS analyses (Table 1)…”
Section: Derivatizationmentioning
confidence: 99%
“…The identification of vanillin at 80, 90 and 100 °C may be due to the thermal degradation of ferulic acid. The small quantification of ferulic acid in all samples and its low concentration at 90 and 100 °C compared to other temperatures may be due to its conversion to vanillin or its demethylation to caffeic acid [ 28 , 29 , 30 ]. It should be highlighted that our samples are very rich in flavonoids; however, the majority of phenolic acids, such as caffeic acid, salicylic acid, vanillic acid and p-coumaric acid, were not identified in such samples.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the phenolic acids are present as trans-isomers, and after exposure to various extreme conditions (more protic solvent, higher temperatures, longer storage times, etc. ), degrade (isomerized) rapidly (Razboršek et al 2021). The rapid decomposition of trans-rosmarinic acid to its cis-isomer in a protic organic solvent was observed by Razboršek (2011).…”
Section: Discussionmentioning
confidence: 98%